Medicinal plants with anti-leukemic effects: A review - Maher, Tahani; Raha, Ahmad Raus; Daddiouaissa, Djabir; Farah, Ahmad; Noor Suhana, Adzahar; Elda Surhaida, Latif; Abdulhafiz, Ferid; Mohammed, Arifullah (MDPI - Open Access Publishing, 2021)
Leukemia is a leukocyte cancer that is characterized by anarchic growth of immature immune cells in the bone marrow, blood and spleen. There are many forms of leukemia, and the best course of therapy and the chance of a patient’s survival depend on the type of leukemic disease. Different forms of drugs have been used to treat leukemia. Due to the adverse effects associated with such therapies and drug resistance, the search for safer and more effective drugs remains one of the most challenging areas of research. Thus, new therapeutic approaches are important to improving outcomes. Almost half of the drugs utilized nowadays in treating cancer are from natural products and their derivatives. Medicinal plants have proven to be an effective natural source of anti-leukemic drugs. The cytotoxicity and the mechanisms underlying the toxicity of these plants to leukemic cells and their isolated compounds were investigated. Effort has been made throughout this comprehensive review to highlight the recent developments and milestones achieved in leukemia therapies using plant-derived compounds and the crude extracts from various medicinal plants. Furthermore, the mechanisms of action of these plants are discussed.